Characterization and Inactivation of an Agmatine Deiminase from Helicobacter Pylori - Jones, Justin E. (2009)
Helicobacter pylori encodes a potential virulence factor, agmatine deiminase (HpAgD), which catalyzes the conversion of agmatine to N-carbamoyl putrescine (NCP) and ammonia - agmatine is decarboxylated arginine. Agmatine is an endogenous human cell signaling molecule that triggers the innate immune response in humans. Unlike H. pylori, humans do not encode an AgD; it is hypothesized that inhibition of this enzyme would increase the levels of agmatine, and thereby enhance the innate immune response. Taken together, these facts suggest that HpAgD is a potential drug target. Herein we describe the optimized expression, isolation, and purification of HpAgD (10–30 mg/L media). The initial kinetic characterization of this enzyme has also been performed. Additionally, the crystal structure of wild-type HpAgD has been determined at 2.1 Å resolution. This structure provides a molecular basis for the preferential deimination of agmatine, and identifies Asp198 as a key residue responsible for agmatine recognition, which has been confirmed experimentally. Information gathered from these studies led to the development and characterization of a novel class of haloacetamidine based HpAgD inactivators. These compounds are the most potent AgD inhibitors ever described.